2008
DOI: 10.1007/s00411-008-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

Skin dose from neutron-activated soil for early entrants following the A-bomb detonation in Hiroshima: contribution from β and γ rays

Abstract: Epilation was reported among atomic bomb survivors in Hiroshima and Nagasaki, including "early entrance survivors" who entered the cities after the bombings. The absorbed dose to the skin by neutron-activated soil via beta and gamma rays has been estimated in a preliminary fashion, for these survivors in Hiroshima. Estimation was done for external exposures from activated soil on the ground as well as skin and hair contamination from activated soil particles, using the Monte Carlo radiation transport code MCNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Unlike systemic exposure to direct radiation by neutrons and gamma rays from the atomic bombs, residual radioactivity would have involved radioactive material in the surrounding environment of the survivor and would have resulted in different exposure modalities. Examples include contact skin dose from fallout that may have been in rain, or beta dose to skin occurring after the end of rainfall from fallout on the ground or other surfaces in the environment, or external exposure from neutron-activated soil materials nearby or adhering to skin (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike systemic exposure to direct radiation by neutrons and gamma rays from the atomic bombs, residual radioactivity would have involved radioactive material in the surrounding environment of the survivor and would have resulted in different exposure modalities. Examples include contact skin dose from fallout that may have been in rain, or beta dose to skin occurring after the end of rainfall from fallout on the ground or other surfaces in the environment, or external exposure from neutron-activated soil materials nearby or adhering to skin (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a small sample of Nishiyama and non-exposed residents were tested for radiological body burdens in 1970 and higher 137 Cs counts were observed among the Nishiyama residents. Radiation dose to the skin from fission fallout and neutron-activated soil has been previously estimated based on the following assumptions in Hiroshima (16,17). Endo et al calculated that if the skin was covered with a 26 lm thick layer of soil contaminated with a fallout radionuclide inventory corresponding to an initial ground deposition of 1 kBq/m 2 -137 Cs, the total beta dose to skin would be about 0.5 Sv for continuous exposure over the one-month period after the explosion (16).…”
Section: Discussionmentioning
confidence: 99%
“…Both from the ABCC/RERF data and other reports, there is no consistent and convincing evidence of a particular directional asymmetry in rates of epilation among distal survivors. It was observed that Culling's 50th-percentile dose estimate for epilation is 2 Gy with an assumed neutron dose weight of 1, significantly less than a 3-Gy threshold described below or the 2-Gy threshold mentioned by Tanaka et al (2008).…”
Section: Survivors Who Experienced Epilation and Their Locationsmentioning
confidence: 92%
“…Monte Carlo simulation of electron transport in biological tissue was performed using MCNP-4C code with the EL03 Library of cross sections for electrons, and beta spectra of different neutron-activated radionuclides were accounted for. Using the standing Japanese human phantom, the cumulative beta dose to the skin of the head approached approximately 0.1 Gy, compared with 0.2 Gy in Tanaka et al (2008) for skin on a vertical surface of the torso at the Hiroshima hypocenter.…”
Section: Estimation Of Contact Beta-particle Exposures To Residual Ramentioning
confidence: 99%
“…Also, activated materials may be likely to have the energy from betas be less than from gamma rays. Tanaka et al (2008) calculated a small skin dose at Hiroshima, for example 0.37 Gy if the hypocenter area is occupied for 7 days after entering 1 h after the bombing. However, only activated soil was considered by Tanaka.…”
Section: Interpreting Excess Tld Dosementioning
confidence: 99%